2008
DOI: 10.1016/j.otohns.2008.05.503
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Liposomal Paclitaxel Raises Tumor Vessel Leakiness

Abstract: Problem Paclitaxel encapsulated in cationic liposomes (EndoTAG-1) is a vascular targeting formulation for the treatment of solid tumors. It triggers intratumoral microthrombosis causing significant inhibition of tumor perfusion and tumor growth associated with endothelial cell apoptosis. Here, we quantified the effects of repeated EndoTAG-1 therapy on tumor microvascular leakiness with respect to leukocyte-endothelial cell interactions, the targeting property of cationic liposomes and the therapeutic combinati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2011
2011

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…It has recently been reported that paclitaxel, doxorubicin, and oxaliplatin encapsulated in CLP exhibited improved antitumor efficacy associated with impaired function of the tumor microvasculature. [8][9][10][11] Campbell et al 12 stated that a positive charge on liposomes is required to enhance their interactions with the glycoprotein layer of the endothelium. However, unshielded CLP or lipoplexes themselves are well known to possess poor physicochemical characteristics for systemic delivery.…”
Section: Introductionmentioning
confidence: 99%
“…It has recently been reported that paclitaxel, doxorubicin, and oxaliplatin encapsulated in CLP exhibited improved antitumor efficacy associated with impaired function of the tumor microvasculature. [8][9][10][11] Campbell et al 12 stated that a positive charge on liposomes is required to enhance their interactions with the glycoprotein layer of the endothelium. However, unshielded CLP or lipoplexes themselves are well known to possess poor physicochemical characteristics for systemic delivery.…”
Section: Introductionmentioning
confidence: 99%